Dynamism in plastome structure observed across the phylogenetic tree of ferns - Lehtonen S; Cardenas GG (OXFORD UNIV PRESS, 2022)
The growing number of completely sequenced fern plastomes has revealed a structurally more dynamic genome than previously thought. Among other structural changes in plastid genome organization, in particular, the boundaries of inverted repeats have undergone expansions and reductions across many fern lineages. In this study, we generated eight new fern plastomes, each representing a different family, to improve the sampling of plastomes in the fern order Polypodiales. We inferred phylogenetic trees using Bayesian, maximum likelihood and parsimony methods and applying different data partitioning strategies. The trees produced under different analytical approaches were similar, consolidating a robust hypothesis of fern phylogeny, but with a few persistent uncertainties. Structural changes in the genomes include the presence of recently found mobile open reading frames that were concentrated in inverted repeats and in large single copy rpoB-psbZ and rps4-psaI regions. Mobile open reading frames are more common in Polypodiineae than in Aspleniineae, and this may be a signal of distinct evolutionary pattern of plastome structure between these two major fern clades.